Critical review on processing technologies and economic aspect of bio-coal briquette production - Rawat S.; Kumar S. (My University, 2025)
The world is looking for alternative energy resources because of the depletion of fossil fuel reservoirs like crude oil, coal, and natural gases in the next few decades. In this aspect, unutilized coal waste and sustainable biomass are considered major energy contributors to convert biomass blended coal fines as high-quality solid briquettes. The present study integrates different briquette processing technologies to develop, coal-biomass-binder, coal-biomass (binderless), coal-binder, and carbonized biomass-binder composites. Briquette application depends upon, availability of waste coal, selection of appropriate biomass among the countless existing biomass stock, thermal-mechanical characteristics of raw material, and progressive advancements in briquetting machines. Present review highly encourages densification of aquatic biomass (water hyacinth, microalgae), activated sludge (municipal solid waste, tannery industry) as well as agro and forest residues (wheat straw, sawdust) to integrate briquetting technology with wastewater treatment or solid waste management. Briefly, the present study covers all aspects of briquette processing and the application of multifunctional bio-binders as cow dung, which act as a desulfurizing agent besides binding to obtain clean coal combustion. Further, cost assessment and budding future research concerned with briquetting technologies are explored to find alternative and sustainable energy routes. © 2021 Taylor & Francis Group, LLC.